Longshot - Francis, Dick, 1920-2010 (Michael Joseph, 1990)
Hot on the heels of his runaway bestseller Straight, Dick Francis once again breaks away from the pack with his dazzling new mystery, Longshot.A starving writer turns to work that will at least pay the bills, but he soon discovers the perils of rural England.His agent had warned that his impulses would kill him, but he didn't listen--not by a longshot.